Peningkatan Creative Thinking Belajar IPA MelaluiModel Pembelajaran Problem Based Learning DanInquiry Pada Siswa Kelas IV SD Muhammadiyah24 Surakarta Tahun Ajaran 2015/2016 - kRESNA, KRESNA (2016)
This study aims to improve creative thinking learning IPA fourth grade students of SD Muhammadiyah Surakarta Academic Year 2015/206 24 through learning model Problem Based Learning and Inquiry. Data collection techniques used were interviews, observation, and documentation. Test the validity using triangulation techniques sources and triangulation methods. The interactive analysis of data reduction, exposure data, and drawing conclusions. The results showed an increase in creative thinking of students in science learning. It can be proved in the achievement indicators of students' creative thinking with the following results: Students get creative in understanding the problem of 30, 43% (pre-cycle) to 84, 78% (cycle II meeting II). Students' creativity in solving problems with an assortment of answers of 26.08% (pre-cycle) to 82.6% (cycle II meeting II). Creatively solve problems in one way and then another way of 17.39% (pre-cycle) to 73.91% (cycle II meeting II). Creative check the answer with the various methods of settlement and create new methods of 21.73% (pre-cycle) to 67.39% (cycle II meeting II). So students with high learning creative thinking of 34.78% (pre-cycle) to 82.6% (cycle II meeting II). This study concludes that through learning model Problem Based Learning (PBL) and Inquiry in science learning can enhance creative thinking fourth grade students of SD Muhammadiyah Surakarta 24 Academic Year 2015/2016. Keywords: Creative Thingking, Learning Model Problem Based Learning (PBL), Inquiry Learning Model